2017
DOI: 10.1128/jvi.02409-16
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor Ccr7 Restricts Fatal West Nile Virus Encephalitis

Abstract: West Nile virus (WNV) is a mosquito-transmitted flavivirus that can cause debilitating encephalitis. To delineate the mechanisms behind this pathology, we studied Ccr7-deficient mice, which afforded us the capacity to study infection in mice with disrupted peripheral cellular trafficking events. The loss of Ccr7 resulted in an immediate pan-leukocytosis that remained elevated throughout the infection. This leukocytosis resulted in a significant enhancement of leukocyte accumulation within the central nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…This expression profile suggests potential compensation by CCL19 for CCR7 and reflects expression profiles documented from cerebrospinal fluid from patients infected with Varicella-Zoster virus [93]. Also, studies in CCR7 deficient mice reported increased death from West Nile virus infection via over-recruitment of leukocytes and inflammation [94]. The reduced activity of CCR7 observed could make PD cells vulnerable to neuropathogens due to enhanced expression towards an inflammatory response.…”
Section: Discussionsupporting
confidence: 55%
“…This expression profile suggests potential compensation by CCL19 for CCR7 and reflects expression profiles documented from cerebrospinal fluid from patients infected with Varicella-Zoster virus [93]. Also, studies in CCR7 deficient mice reported increased death from West Nile virus infection via over-recruitment of leukocytes and inflammation [94]. The reduced activity of CCR7 observed could make PD cells vulnerable to neuropathogens due to enhanced expression towards an inflammatory response.…”
Section: Discussionsupporting
confidence: 55%
“…Chemokines' principle role is in orchestrating the inflammatory and both adaptive and innate immunological responses; and in particular, controlling migration and function of various leukocytes including eosinophils, neutrophils, and basophils as well as T and B lymphocytes [6]. More recently however, chemokines and their receptors are shown to be involved in a wider range of physiological and pathophysiological processes ranging from directing sperms movement towards the ovum [7] to asthma [8], rheumatoid arthritis [9], atherosclerosis [10], and viral infection [11][12][13][14]. In particular, many chemokine axes are shown to have a multifaceted involvement in cancer [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…CCR7 regulates trafficking of leukocytes to and within the lymphatic system [ 49 ]. In CCR7-/- mouse models, circulating leukocytes are significantly increased and elevated numbers of monocytes migrate into tissues where they can cause damage [ 50 , 51 ]. This observation together with our previous findings suggest that in acute HFRS patients with higher monocyte CCR7 levels, CCR7 may regulate monocyte migration to lymph nodes instead of unchecked peripheral tissue infiltration and possibly, subsequent immune-mediated damage.…”
Section: Discussionmentioning
confidence: 99%